ChemInform Abstract: [2 + 2] Photocycloaddition of Cinnamates in Flow and Development of a Thiourea Catalyst. Issue 6 (21st January 2016) - Telmesani, Reem; Park, Sung H.; Lynch‐Colameta, Tessa; Beeler, Aaron B.
Abstract: The bis(thiourea)‐catalyzed dimerization of cinnamates (I) in a flow photoreactor gives rise to diaryl‐cyclobutanedicarboxylates as a mixture of diastereomers (II) and (III).